PENGARUH E-WOM DI MEDIA SOSIAL YOUTUBE TERHADAP PURCHASE INTENTION (MINAT BELI) PADA BRAND SMARTPHONE SAMSUNG - Sari, Ketut Dewi Kurnia; Sharif, Osa Omar (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.10.NO.09.TAHUN.2021, 2021)
This study aims to determine how the influence of the Electronic Word of Mouth (eWOM) on social media YouTube on Purchase Intention on Samsung smartphones in Bandung with the presence of a mediator from Brand Attitude. The research method used is a quantitative method with descriptive research objectives, the type of research is causal, the technique used in this study is non-probability sampling, data collection methods with cross sectional. In this study, the population used in this study were smartphone users in Bandung. The population in this study were smartphone users in Bandung who used social media Youtube. The sampling technique used the Cochran formula so that a minimum sample size of 385 respondents was determined and in the study the valid respondents were 400 respondents. The data analysis technique is a multivariate technique using the Structural Equation Modeling (SEM) method. For data analysis using the AMOS 24 application. The findings of this study indicate that there is no effect of eWOM Samsung smartphones on Purchase Intention and the influence of eWOM on the Brand Attitude of Samsung brand smartphones on Youtube social media